3
$\begingroup$

Let $\Omega \subset \mathbb{R}^2$ be open, bounded and symmetric with respect to the origin. Let$ f:\partial \Omega \to \mathbb{R} $ be odd and continuous function. Show that if $u$ is solution of:

$$ \begin{cases} \Delta u(x)&=0,&\text{ if }x \in \Omega \\ \phantom{-}u(x)&=f(x),&\text{ if }x \in \partial\Omega \end{cases} $$

then $u$ is odd.

Hint: study of the Laplacian's invariance in relation to $T(x,y)=(-x,-y)$

I tried to show that $\Delta u= \Delta (u\circ T)=0$, but how to finish?

$\endgroup$
4
$\begingroup$

If you show that $\Delta (u\circ T)=0$ in $\Omega$ you're done by uniqueness.

Indeed, first note that since $\Omega$ is bounded and symmetric with respect to the origin then $(x,y)\in\partial\Omega$ iff $(-x,-y)\in\partial\Omega$. Then, using that $f$ is odd and $u$ a solution we have for all $(x,y)\in\partial\Omega$ $$u(x,y)=f(x,y)=-f(-x,-y)=-u(-x,-y)=-(u\circ T)(x,y).$$ Now, as you noted $\Delta(u\circ T)=0$, which follows by symmetry of $\Omega$ and the identities for all $(x,y)\in\Omega$ $$\partial^2_x(u\circ T)(x,y)=\partial^2_xu(-x,-y),\\\partial^2_y(u\circ T)(x,y)=\partial^2_yu(-x,-y).$$ Finally, this implies that both $u$ and $-(u\circ T)$ are solutions to your Dirichelt problem. The fact the $f$ is continuous implies that you only have one solution, hence $$u(x,y)=-(u\circ T)(x,y)=-u(-x,-y)$$ for all $(x,y)\in\mathbb{R}^2$.

Note: While I was writing this, another answer was posted. The solution is essentially the same: maxima principle $\Rightarrow$ uniqueness.

$\endgroup$
  • $\begingroup$ I lost a bit in the derivatives. $\frac{\partial u}{\partial x}(-x,-y)=-\frac{\partial u}{\partial x}(x,y)$, Right? $\endgroup$ – Lucas May 15 at 22:04
  • $\begingroup$ The chain rule reads $\partial_x(u\circ T)(x,y)=\partial_xu(T(x,y))\partial_xT(x,y)=-\partial_xu(-x,-y)$. $\endgroup$ – pipenauss May 16 at 12:26
3
$\begingroup$

If you already showed that $\Delta u(-x, - y) =0$, take $v=u(x, y) +u(-x, - y) $.

By the fact that f is odd, $v$ is solution for the problem: \begin{equation} \begin{cases} \Delta v=0 \\ v=0, \ \ \ in \ \partial \Omega \end{cases}\end{equation}

So, by the maxima principle $v=0$ in $\Omega $ then $u(x, y)=-u(-x, - y) $ in $\Omega$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.